The Rationality of Action and the Dynamics of Social Piety: An Analysis of Motivations within the Muslim Community Participating in the Haul Akbar Tradition in West Lombok - Maya Mahika (Tabéq Care Center and UIN Mataram, 2026)
The tradition of commemorating the passing of religious figures (haul) constitutes an integral component of the socio-religious landscape among Muslim communities throughout the Indonesian archipelago, including West Lombok. This study seeks to systematically analyse and describe the motivations underlying the high level of participation by the Muslim community in the Haul Akbar of TGH Ridwanullah At-Tauhidy in Babussalam Village. The phenomenon is examined through the theoretical framework of Max Weber’s rationality of social action. Employing a descriptive qualitative approach, data were collected through participatory observation, in-depth interviews, and documentation. The findings indicate that community attendance is motivated by two principal categories: intrinsic motivations, such as the pursuit of spiritual peace and the strategic aim of enhancing religious knowledge; and extrinsic motivations, shaped by cultural pressures within religious family environments and the charisma of TGH Ridwanullah At-Tauhidy. A Weberian analysis further identifies four pillars of action: traditional action in preserving local identity, affective action for emotional and spiritual fulfilment, instrumental rational action to address theological ignorance, and value-rational action expressed through devotion to the example set by the ulama. Thus, the haul serves as more than a death-commemoration ritual; it represents a complex sociological arena that continually fosters communal piety, reinforces social solidarity, and perpetuates a culture of mutual aid in the contemporary era.